Pengaruh Pemberian Reward Terhadap Minat Belajar Siswa Pada Mata Pelajaran PAI di SMPN 2 Nan Sabaris Kabupaten Padang Pariaman - Lestari, Ayu; Yusra, Oktarina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The poor curiosity about class VIII Islamic Religious Education students' background topics at SMPN 2 Nan Sabaris, Padang Pariaman Regency, inspired this study. The absence of feedback between instructors and students, the lack of attention of students when the teacher explains the courses, shows that the motivation of class VIII students in studying in Islamic Religious Education is still poor at SMPN 2 Nan Sabaris Padang Pariaman Regency. Thus, this study is to investigate if rewarding students in the Islamic Religious Education class VIII SMPN 2 Nan Sabaris Padang Pariaman Regency influences their enthusiasm in studying. Although the study technique is correlational, the kind of research carried out is quantitative. Two variables make up this study variable: y, variabel terikat; variabel independen (x), of which the former is incentives and the latter students' enthusiasm in learning. 66 class VIII pupils from SMPN 2 Nan Sabaris, Padang Pariaman Regency, 2023/2024 academic year comprised the population of this research. Saturated or total samples are used in sampling such that the whole population is chosen as the sample. Students participate in a questionnaire on incentives and enthusiasm in learning, therefore gathering data. Giving prizes to pupils influences their enthusiasm in studying at the SMPN 2 Nan Sabaris, Padang Pariaman Regency class VIII Islamic Religious Education course. The statistical test reveals that the t value = 3.173 with a significance value of 0.002 indicates Ho rejected and Ha accepted, so influencing students' interest in learning in Islamic Religious Education subjects at SMPN 2 Nan Sabaris Padang Pariaman Regency.